Leveraging Nurses to Improve Care for Patients with Concurrent Disorders in Inpatient Mental Health Settings: A Scoping Review. Issue 3 (2nd July 2020) - Garrod, Emma; Jenkins, Emily; Currie, Leanne M.; McGuinness, Liza; Bonnie, Kofi
Abstract: Objective: Several challenges have been identified for patients with concurrent disorders and the providers that care for them, contributing to a pressing need for interventions to improve outcomes, particularly within inpatient mental health settings. Methods: A systematic search of peer-reviewed literature was conducted using four online databases: CINAHL, MEDLINE (Ovid), PsycInfo and Web of Science. Articles were selected based on inclusion criteria and additional articles were identified through hand searches. Study details were charted and qualitative synthesis was conducted. Results: Thirty two articles met inclusion criteria. A substantial focus within the literature was education, with higher levels of education shown to improve healthcare provider attitudes and practices. Within this overarching focus, four themes were identified: 1) education as an intervention to improve attitudes and increase confidence and knowledge; 2) strategies to support practice change, including interventions aimed at clinical leaders and methods to address substance use among inpatients; 3) frameworks to guide care; and 4) opportunities to expand nursing scope of practice. Conclusions: Given the substantial evidence indicating that education improves nurses' knowledge, attitudes and practices, there is great promise in expanding educational intervention opportunities for nurses to improve care and outcomes for patients with concurrent disorders—a priority patient population.